ANALISIS PENDAPATAN PADA BALAI PENGOBATAN SANTA FAMILIA BARONG TONGKOK KUTAI BARAT - MAYANG, FIRMINA MAYANG (EKONOMIA, 2018)
Income Analysis at Balai Keluarga Santa Familia Barong Tongkok under the advisory of Mr. LCA. Robin Jonathan as advisor I and Mrs. Elfreda Aplonia Lau as advisor II. The purpose of this study was to find out and analyze the income and residual business results of Santa Familia Treatment Center and know the level of revenue growth in 2013 and 2014. The research problems were formulated as follows:1. Are the Income and Residual Business Results of Santa Familia Medical Center in 2013 having a targeted growth of 30%?2. Are the Income and Residual Business Results of Santa Familia Medical Center in 2014 experiencing a targeted growth of 30%? The basic theory used in this study was the theory of Financial Management that focused on income and growth.Hypothesis as follows:1. Operating Income and Residual Business Results of Santa Familia Medical Center in 2013 has not reached the target of profit of 30%.2. Operating Income and Residual Business Results of Santa Familia Medical Center in 2014 has not reached the target of profit of 30%. The result of analysis showed that: first, thr growth of income and Residual Businness Results in 2012 and 2013 did not reach the target so that this hypothesis was accepted. Second, this reseaech is accepted if the income and the residual Business Results in 2014 reached the target as expected by management of Santa Familia Medical Center Barong Tongkok